Global biodiversity and the expanding Tree of Life - John J. Wiens; Ellerie G. Blomenkamp; Miles Corliss; Xin Li (Proceedings of the National Academy of Sciences, 2026)
Global biodiversity is increasingly threatened, but still poorly known. Preserving higher taxa (e.g., genera, families, orders) is especially important because each higher taxon may represent more genetic, morphological, ecological, and functional diversity than a typical species within a genus. Given this, there has been considerable focus on the loss of clades and their phylogenetic diversity. However, we know little about whether there are also gains of new clades: new higher taxa that are based on newly discovered species. Here, we analyze these newly discovered branches across the Tree of Life. We estimate that >700 new genera, >20 new families, and >3 new orders are described every year, each associated with newly discovered species. The distribution of new genus-level clades largely reflects current species richness patterns among groups. Thus, they are dominated by terrestrial arthropods. At higher taxonomic ranks, the distribution of new clades among groups is increasingly unrelated to the current, known species richness of these groups, and fungi and bacteria predominate. New clades are increasingly microscopic at higher taxonomic ranks and are often marine or host associated. Overall, we suggest that the known Tree of Life is continuing to rapidly expand with many newly discovered clades, not merely contracting with recent extinctions. Discovering and describing these new clades before they disappear should be an urgent research priority. There is also a pressing need to better incorporate phylogenies into the discovery of these new higher taxa.